Venous Thromboembolism Prevention in the Hospitalized Medical Patient - Tsaftaridis, Nikolaos; Cholagh, Anthony; Kaatz, Scott; Spyropoulos, Alex C (The Medical clinics of North America, 2025)
Acutely ill hospitalized medical patients are at a higher risk of venous thromboembolism (VTE) compared to the general population. A universal thromboprophylaxis strategy upon admission is inadequate as it fails to consider individual patient VTE and bleeding risk factors. Validated risk assessment models help identify patients at elevated risk for VTE or bleeding, facilitating appropriate thromboprophylaxis. Extended VTE thromboprophylaxis should be considered in high VTE risk patients at low bleed risk upon discharge as VTE risk can remain increased for up to 45 days postdischarge.